Virulence of blastospores of Isaria fumosorosea natives of northeastern Mexico on Anastrepha ludens (Diptera: Tephritidae). (2018)
Anastrepha ludens is one of the pests that seriously affects fruit production in Mexico and other Neotropical countries. The aim of this study was to evaluate the virulence and effects of four native isolates and a collected strain of Isaria fumosorosea on the metamorphosis of A. ludens through the use of bioassays under laboratory conditions [25 ± 2 °C; 60 ± 5 % (HR); 12:12 h (L: O)]. Larvae and pupae were exposed to 1 × 108 blastospores/ ml using two different methods: direct spraying and spraying of soil. The isolates HIB-23 and HIB-30 showed the highest mortality on A. ludens when applied using the direct spraying method on larvae (84 %), while the isolate HIB-19 showed the highest percentage of interruption of the metamorphosis (43 %) of A. ludens when applied through the method of direct spraying on pupae. The results show that A. ludens is susceptible to the attack of I. fumosorosea, which causes the disruption of its life cycle.